Consolidation of complex-shape zircon compacts through agar gelation. Issue 1 (31st December 2022) - Rosado, Eduardo; Alcázar, Carmen; Recio, Paloma; Moreno, Rodrigo
Abstract: Zirconium silicate (zircon, ZrSiO4) is a ceramic material with excellent thermal properties, such as low thermal conductivity and high thermal shock resistance. In this work, dense zircon complex shaped parts were obtained by aqueous gelcasting through agar gelation. The colloidal stability study was performed through zeta potential measurements as a function of pH and polyacrylic-based deflocculant concentration (PAA). The rheological study was carried out varying the solids content, the dispersant concentration, and the sonication mixing time, the best results being obtained for 0.1 wt.% PAA and 1 min sonication. The viscosity versus temperature curves were recorded on cooling for the zircon-agar mixtures showing a gelling temperature of approximately 35 °C. Better gelcasting performance was achieved with suspensions prepared at a solids loading of 40 vol.%. Dynamic sintering (25–1550 °C) and isothermal sintering tests (1550 °C and 1600 °C) were carried out, studying the shrinkage and densification of the material. Finally, the evolution of phases and the microstructure of the sintered parts were studied using X-ray diffraction (XRD) and scanning electron microscopy (SEM). Relative densities of 94.5% TD were reached at 1600 °C/2 h, but increased to 96% with 8 h holding, with a small grain size increase from 1.8 to 2.4 µm.